2013
DOI: 10.1002/jssc.201200921
|View full text |Cite
|
Sign up to set email alerts
|

Screening for illicit and medicinal drugs in whole blood using fully automated SPE and ultra‐high‐performance liquid chromatography with TOFMS with data‐independent acquisition

Abstract: A broad forensic screening method for 256 analytes in whole blood based on a fully automated SPE robotic extraction and ultra-high-performance liquid chromatography (UHPLC) with TOF-MS with data-independent acquisition has been developed. The limit of identification was evaluated for all 256 compounds and 95 of these compounds were validated with regard to matrix effects, extraction recovery, and process efficiency. The limit of identification ranged from 0.001 to 0.1 mg/kg, and the process efficiency exceeded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 32 publications
(52 reference statements)
1
46
0
Order By: Relevance
“…A large number of drugs can be included, since evidence regarding impairment is not requested. Denmark has fixed-concentration limits, and more than 200 substances are included in the screening analysis [39]. The penalty is loss of driving license and a fee.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of drugs can be included, since evidence regarding impairment is not requested. Denmark has fixed-concentration limits, and more than 200 substances are included in the screening analysis [39]. The penalty is loss of driving license and a fee.…”
Section: Discussionmentioning
confidence: 99%
“…The LODs were at least 1 mg/kg blood, and all samples had to be injected twice: one time in positive and one time in negative ionization mode. The second procedure (Pedersen et al 2013) reported LODs typically below 0.1 mg/kg blood, and identification criteria were identical to those by Dalsgaard et al The analysis covered 256 compounds, but only for 95 compounds, matrix effect, extraction recovery, and process efficiency were studied. Most of the common DoA could be detected by this approach with the exception of delta-9-tetrahydrocannabinol.…”
Section: Testing Of Pharmaceuticals In Emergency Toxicologymentioning
confidence: 92%
“…The group of Linnet presented two screening procedures based on this data-independent principle: one optimizing a previously described system for screening of 30 acidic and neutral drugs in whole blood (Dalsgaard et al 2013) and one as broad forensic screening method in whole blood samples both after fully automated off-line SPE robotic extraction (Pedersen et al 2013). The first procedure identified compounds based on retention time (0.2 min window) and the presence of one fragment ion and/or isotopic pattern.…”
Section: Testing Of Pharmaceuticals In Emergency Toxicologymentioning
confidence: 99%
“…The manuscript with its real and imaginative title, "Taking the Pissoira novel and reliable way of knowing what drugs are being used in nightclubs", reported the detection of classical recreational drugs and NPSs such as: mephedrone, 3′-trifluoromethylphenylpiperazine and 2-aminoindane using various chromatographic and mass spectrometric methods. 44 Earlier reports in Denmark, Pedersen et al 35 presented an automated solid-phase extraction (SPE) and ultra-highperformance liquid chromatography (UHPLC) with time of flight-mass spectrometry (TOF-MS) screening method for 256 illicit compounds in blood and 95 of these compounds were validated with regard to matrix effects, extraction recovery, and process efficiency with the limit of detection (LOD) ranging from 0.001 to 0.1 mg kg −1 . 19 In the same year, Leffler et al 44 (located in the United States) analysed 14 separate street samples wherein 10 synthetic cathinones were identified employing a variety of techniques, including gas chromatography with mass spectrometric detection (GC-MS) and flame ionization (GC-FID).…”
Section: Synthetic Cathinonesmentioning
confidence: 95%